2015
DOI: 10.1124/dmd.115.067785
|View full text |Cite
|
Sign up to set email alerts
|

Tariquidar Is an Inhibitor and Not a Substrate of Human and Mouse P-glycoprotein

Abstract: Since its development, tariquidar (TQR; XR9576;4-dihydro-1H-isoquinolin-2-yl)ethyl]phenyl]carbamoyl]-4,5-dimethoxyphenyl]quinoline-3-carboxamide) has been widely regarded as one of the more potent inhibitors of P-glycoprotein (P-gp), an efflux transporter of the ATP-binding cassette (ABC) transporter family. A third-generation inhibitor, TQR exhibits high affinity for P-gp, although it is also a substrate of another ABC transporter, breast cancer resistance protein (BCRP). Recently, several studies have questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 24 publications
(39 reference statements)
2
57
0
Order By: Relevance
“…Cyclosporin A, a substrate for P-gp, blocks the pumping of drugs in a competitive manner [55] and inhibits drug-activated and basal ATPase activity of P-gp [56]. Tariquidar, a potent inhibitor of P-gp [57, 58], but also a substrate and inhibitor for breast cancer resistance protein (BCRP/ABCG2) [59], shows a noncompetitive interaction with P-gp substrates and inhibits the ATPase activity of P-gp [60]; it could thus be considered to have an allosteric effect on substrate recognition or ATP hydrolysis. There is also a report showing that tariquidar inhibits P-gp drug efflux by blocking transition to the open state during the catalytic cycle [61].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A, a substrate for P-gp, blocks the pumping of drugs in a competitive manner [55] and inhibits drug-activated and basal ATPase activity of P-gp [56]. Tariquidar, a potent inhibitor of P-gp [57, 58], but also a substrate and inhibitor for breast cancer resistance protein (BCRP/ABCG2) [59], shows a noncompetitive interaction with P-gp substrates and inhibits the ATPase activity of P-gp [60]; it could thus be considered to have an allosteric effect on substrate recognition or ATP hydrolysis. There is also a report showing that tariquidar inhibits P-gp drug efflux by blocking transition to the open state during the catalytic cycle [61].…”
Section: Discussionmentioning
confidence: 99%
“…A recent comprehensive analysis of the interactions of the third generation inhibitor, tariquidar, with P‐gp demonstrated that tariquidar does not behave as a P‐gp substrate. BCRP was suggested as the major transporter that mediates tariquidar's removal from the brain . The current absence of PET markers that bind with high affinity to P‐gp or BCRP complicates transporter expression studies in humans.…”
Section: The Value Of Transporter Imagingmentioning
confidence: 99%
“…Several studies report that miRNAs can regulate MDR by modulating the expression of P-gp. For example, it has been shown that miR-451 and miR-27a upregulation was P-gp dependent in cell lines representing ovarian cancer, leukemia and hepatocellular carcinoma [112,114,115] . In contrast, deregulation rather than upregulation of certain miRNAs, such as miR27a and miR 331-5p, can also cause drug resistance reversal and decreased P-gp expression, as seen in doxorubicin resistant leukemia cell lines K562 and HL60 [131][132][133] .…”
Section: The Role Of Micrornas In P-gp Modulationmentioning
confidence: 99%
“…Since its discovery, tariquidar was described as non-competitive and non-transported inhibitor of P-gp [110] , while Bankstahl et al [111] have shown that tariquidar is concentration-dependently transported by P-gp. Recent transepithelial drug transport assays using radioactive tariquidar in human and mouse cell lines indicate that tariquidar functions as a high-affinity P-gp substrate rather than a non-competitive inhibitor [112] .…”
Section: Inhibition Of P-gpmentioning
confidence: 99%
See 1 more Smart Citation